The Role of Symbolism in Understanding Edgar Allan Poe’s Short Story: A Case Study of The Fall of The House of Usher - Huda, Hisnul Mar’atil; Nasirin, Nasirin (Jurnal Ilmiah Profesi Pendidikan, 2023)
This study aims to analyze the role of symbolism in understanding Edgar Allan Poe's short story, “The Fall of the House of Usher.” The research method used is a case study with a qualitative approach. Data collection was conducted through in-depth textual analysis of the short story, focusing on identifying and interpreting the main symbols within the narrative. The data analysis technique employed is content analysis, where data is systematically analyzed to identify symbolic themes and uncover hidden meanings behind these symbols. The results of the study indicate that symbolism plays a crucial role in building the atmosphere and themes of the story, as well as providing depth to the characters and plot. The conclusion of this study is that symbolism in "The Fall of the House of Usher" not only enriches the reader's experience but also reveals deeper insights into the psychological conditions of the characters and the dark themes explored by Poe. The implications of this study highlight the importance of understanding symbolism in literary works to gain a more comprehensive interpretation.